Parental perceptions and responses to stuttering in their children: A qualitative study from Saudi Arabia - Almutairi, Mohammed Abdulaziz (Edelweiss Applied Science and Technology, 2025)
This qualitative study explores how Saudi parents understand and respond to stuttering in their children. Focus groups were conducted with 30 parents of children aged 2 to 12 years who stutter. Parents described diverse beliefs about the causes of stuttering, though many of these views did not fully align with current scientific understanding. Most parents reported seeking professional help primarily in response to observable secondary behaviors (e.g., physical movements during speech). While speech-language pathologists (SLPs) were the most trusted source of information, some parents also used digital platforms to better understand and manage stuttering. Some parents had experience managing stuttering using technology such as delayed auditory feedback (DAF) devices or apps; however, these were often discontinued due to technical issues, discomfort, or challenges with classroom usability. The study recommends applied, evidence-based strategies to improve parental support, including targeted educational initiatives, stronger communication between SLPs and families, and user-friendly resources to support home practices. It also highlights the value of interdisciplinary collaboration, where professionals from fields such as speech-language pathology (SLP), psychology, and education work together to address stuttering from integrated perspectives. These findings have practical implications for educators and developers of technology-based tools for the management of stuttering and support broader efforts to strengthen early intervention and caregiver engagement in fluency disorders.